Answer:
![\huge\boxed{\sf \$ \ 26.24}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7B%5Csf%20%5C%24%20%5C%2026.24%7D)
Step-by-step explanation:
Each side of the squared painting = 41 inches
A square has 4 sides. So,
4 sides of the square painting = 4(41) inches
= 164 inches
![\rule[225]{225}{2}](https://tex.z-dn.net/?f=%5Crule%5B225%5D%7B225%7D%7B2%7D)
<u>The shop charges:</u>
1 inches = $ 0.16
Multiply both sides by 164
164 inches = $ 0.16 × 164
164 inches = $ 26.24
![\rule[225]{225}{2}](https://tex.z-dn.net/?f=%5Crule%5B225%5D%7B225%7D%7B2%7D)
Hope this helped!
<h2>~AnonymousHelper1807</h2>
Answer:
the answer is C.-1/128......
Answer:
![8x^{3}-34x^{2}+25x-3](https://tex.z-dn.net/?f=8x%5E%7B3%7D-34x%5E%7B2%7D%2B25x-3)
Step-by-step explanation:
In order to solve this problem, lets take the two terms in the binomial (4x and -3) and, for each one, multiply them by each term in the trinomial (2x^2, -7x, and 1):
![(4x-3)(2x^{2}-7x+1)](https://tex.z-dn.net/?f=%284x-3%29%282x%5E%7B2%7D-7x%2B1%29)
![(4x*2x^{2})+(4x*-7x)+(4x*1)+(-3*2x^{2})+(-3*-7x)+(-3*1)](https://tex.z-dn.net/?f=%284x%2A2x%5E%7B2%7D%29%2B%284x%2A-7x%29%2B%284x%2A1%29%2B%28-3%2A2x%5E%7B2%7D%29%2B%28-3%2A-7x%29%2B%28-3%2A1%29)
![8x^{3}+(-28x^{2})+4x+(-6x^{2})+21x+(-3)\\](https://tex.z-dn.net/?f=8x%5E%7B3%7D%2B%28-28x%5E%7B2%7D%29%2B4x%2B%28-6x%5E%7B2%7D%29%2B21x%2B%28-3%29%5C%5C)
![8x^{3}-28x^{2}+4x-6x^{2}+21x-3](https://tex.z-dn.net/?f=8x%5E%7B3%7D-28x%5E%7B2%7D%2B4x-6x%5E%7B2%7D%2B21x-3)
Let's combine like terms to get our final answer:
![8x^{3}-28x^{2}-6x^{2}+4x+21x-3](https://tex.z-dn.net/?f=8x%5E%7B3%7D-28x%5E%7B2%7D-6x%5E%7B2%7D%2B4x%2B21x-3)
![8x^{3}-34x^{2}+25x-3](https://tex.z-dn.net/?f=8x%5E%7B3%7D-34x%5E%7B2%7D%2B25x-3)
Answer:
x = 2
Step-by-step explanation:
5x - 2 = 10 - x
<em>Add x to both sides</em>
6x - 2 = 10
<em>Add 2 to both sides</em>
6x = 12
<em>Divide both sides by 6</em>
x = 2
Answer:
Step-by-step explanation:
<u>Given recursive formula</u>
- a₁ = 0
- aₙ = 2(aₙ₋₁)² - 1, for n>1
<u>The first 5 terms are:</u>
- a₁ = 0
- a₂ = 2(0)² - 1 = 0 - 1 = -1
- a₃ = 2(-1)² - 1 = 2 - 1 = 1
- a₄ = 2(1)² - 1 = 2 - 1 = 1
- a₅ = 2(1)² - 1 = 2 - 1 = 1